2018
DOI: 10.5137/1019-5149.jtn.23081-18.2
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural venous angioma presenting symtomps of lumbar disc herniation: a case report

Abstract: Spinal epidural venous angiomas are extremely rare. We report the case of a 60-year-old man who presented with disc herniation symptoms, complaining of pain in his left leg and numbness, especially at the base of the knee. On physical examination, the Lasègue test was positive at 45 degrees on the left side and no neurological deficit was detected on the lower extremity. Contrast enhanced magnetic resonance imaging revealed a lesion in the left S1 neural foramen, which was initially evaluated as a schwannoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Extradural venous angiomas are the most uncommon subtype of spinal vascular malformations ( 2 , 3 ). Damage to the movement and differentiation of the primitive mesoderm is widely recognized as the cause of spinal vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extradural venous angiomas are the most uncommon subtype of spinal vascular malformations ( 2 , 3 ). Damage to the movement and differentiation of the primitive mesoderm is widely recognized as the cause of spinal vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the etiology of spinal vascular malformations remains unclear ( 4 ). Only six cases of purely extradural spinal venous angiomas have been reported since 1978 during which the first case was reported by Decker et al A review of these six cases showed that almost all patients presented with somatic pain, numbness, or limb weakness ( 2 , 3 ). During the early stage, the patient's symptoms were fairly insidious, leading doctors to ignore them until the enlargement of the intralesional hemorrhage caused other symptoms ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, contrast MRI showed a heterogeneous enhancing pattern in eight cases, ring enhancement in two cases, and no enhancement in one case. Of the eight cases showing heterogeneous enhancing pattern, one case was an arteriovenous hemangioma 8) , and one was a venous hemangioma 9) ; the remaining six cases were all cavernous hemangioma. However, three patients have relatively acute onset of symptoms of 6 h 10) , 3 days 11) , and 8 days 10) .…”
Section: Symptomsmentioning
confidence: 97%